The IMPACT OF DEMOGRAPHY AND PERCEPTION ON MALE CONTRACEPTIVE USE IN INDONESIA: Contraceptive Use - Yunita Amraeni; Sudijanto Kamso (STIKes Mandala Waluya Kendari, 2021)
Background: Increasing men's empowerment in family planning and reproductive health is needed, one of the ways is by deepening the understanding of the factors that encourage the participation of husbands as family planning acceptors. This study aims to determine the relationship between knowledge, education and husband's perceptions of family planning with the participation of husbands as family planning acceptors in Indonesia. Methods: A cross sectional study design using the 2017 IDHS basic data with a sample of 3,751 respondents. Qualitative study on 20 husband with indepth interview also using to explore the perception on contraception. The study used univariable and bivariable analysis with Chi-square test. Results: The results showed that the variables of husband's knowledge, education and perceptions about family planning had a significant relationship with each p-value = 0,000 smaller than ? = 0.05. Most of husband argues men should not be involved in family planning because it is related to culture and fear of side effects. Conclusion: The low percentage of husband's participation in family planning shows that efforts to continue to increase the husband's participation rate into family planning acceptors must continue to be encouraged.